Artistic representation of the imperial leadership and its delegation in Sicily of Charles V - Peláez Márquez, José María; Pérez Araújo, Álvaro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper shows the possibility of using the Humanities in the training of managers by combining two apparently diverse sciences. After defining the main functions of a manager, these functions are identified in the artistic representations of Emperor Charles V and his main viceroy in Sicily. This analysis of their leadership capabilities is carried out following a method known in the area of Human Resources Management as Assesment Center that values through the actions of those evaluated and third-party testimonials the quality of leadership. As a result, we will see that the works analyzed serve to illustrate concepts related to business management so that Art can be used as an effective tool in the training of managers, which indicates its transversality to the other sciences.